The extent of application of digital transformation standards to the management of the services of the Ministry of Justice, Madinah branch, from the staff viewpoint - Al-Sulami, Majed Attia; Rajkhan, Dana Munther; Al-Mutairi, Hadeel Khalaf (Journal of Economic, Administrative and Legal Sciences, 2025)
The Kingdom of Saudi Arabia aims to enhance digital transformation across its governmental services to improve the quality and efficiency of services provided to citizens and residents. The Ministry of Justice in the Madinah branch faces significant challenges in integrating digital technologies into its service management, highlighting a gap in current research evaluating the impact of digital transformation on the ministry's service management. This study aims to assess the extent to which digital transformation criteria are applied in the Ministry of Justice’s service management in the Madinah branch and analyze the impact of these criteria on service performance from the perspectives of employees and administrators.Accordingly, the study hypothesizes that there is a statistically significant relationship between the application of digital transformation criteria and the improvement in service quality and efficiency. It also anticipates statistically significant differences in the impact of digital transformation on service performance based on different administrative specialties and believes that there is a statistically significant relationship between the technical and administrative challenges in implementing digital transformation and the level of performance improvement and work efficiency.The study employed a descriptive survey method, distributing a questionnaire to Ministry employees and analyzing the data using SPSS software. The results indicated a noticeable improvement in service performance due to digital transformation, with increased efficiency, reduced costs, and enhanced service quality. The study recommends strengthening digital transformation efforts, investing more in employee training, improving quality management, and focusing on change management and periodic reporting to monitor administrative reforms.
Keywords: Digital Transformation Standards; Service Management; Ministry of Justice